Morphofunctional And Clinical Evaluation Of Spirulina’s Role In Accelerating Recovery Following Physical Stress - Jalalova Vazira Zamirovna (International Journal of Medical Sciences And Clinical Research, 2025)
In the context of intensive physical exertion commonly encountered by athletes, the optimization of recovery mechanisms remains a critical challenge for enhancing performance and preventing injury. This study investigates the impact of spirulina, a natural source rich in antioxidants and bioactive compounds, on morphofunctional alterations in skeletal muscle and myocardial tissues in a rodent model subjected to exhaustive physical stress. Furthermore, the study evaluates spirulina’s efficacy within metabolic support regimens for athletes. Experimental data reveal significant improvements in morphometric parameters and immunohistochemical markers, indicating attenuation of tissue damage and acceleration of regenerative processes. Complementary clinical trials involving young athletes demonstrated notable enhancements in functional performance metrics and increased physical endurance following dietary supplementation with spirulina. These results provide robust evidence supporting spirulina’s role as an efficacious metabolic adjunct, facilitating recovery optimization and augmenting athletic capacity.